THE TUBULAR ELEMENTS OF METAL STRUCTURES WITH FLATTENED END FACE - Alexander Surenovich Marutyan; Tamazy Leonidovich Kobaliya (Современная наука и инновации, 2022)
The results of experimental studies of tubular elements with tapered ends are adduced. The prospects of their application in the modernization of metal constructions of buildings and structures are shown